Heavy metal contamination and associated health risk assessment in groundwater of Mirzapur, Uttar Pradesh - Tripathi, Piyush; Varma, Kriti; Srivastava, Vaishali; Dlamini, Nkululeko Sabelo; Jha, Pawan Kumar (Frontiers in Water, 2025)
Groundwater quality assessment is crucial for understanding the effects of natural and anthropogenic activities on water resources, particularly in regions like Uttar Pradesh, India, where groundwater serves as a primary source for drinking, irrigation, and industrial purposes. This study examines the hydrogeochemical characteristics, metal pollution indices, and groundwater quality in relation to carcinogenic and noncarcinogenic risks to adult and child populations, using an integrated approach that combines several metal pollution indices. The analysis is based on 50 samples (25 samples per season) collected in Mirzapur district. The mean concentration of heavy metals in the pre-monsoon phase followed the order: Zn > Fe > Cd > As> Pb > Cr, and during the post-monsoon, it was: Fe > Zn > Cd > As > Pb > Cr. This reversal in the relative abundance of Zinc and Iron likely reflects post-monsoon mobilisation of Fe through reductive dissolution of Fe-bearing minerals, coupled with dilution and leaching effects that reduce Zn concentrations during recharge. The study revealed elevated concentrations of arsenic (100 μg/L) and cadmium (125 μg/L), along with high values of HPI (2900), HEI (47), and NI (34). All of these exceeded the critical values, indicating significant pollution by heavy metals in the region. Chronic exposure to Fe and Cd exhibited Hazard Quotient (HQ) values far above safe thresholds of 1, reaching up to 1.25 for Fe and 3 for Cd. The Total Carcinogenic Risk (TCR) values for As exceeded the acceptable range, reaching up to 4 × 10−3, and particularly impacted vulnerable groups, such as children.